Resilience of primary food production to a changing climate: on-farm responses to water-related risks - Hess, Tim M.; Knox, Jerry W.; Holman, Ian P.; Sutcliffe, Chloe (MDPI, 2020)
Water is a fundamental component in primary food production, whether it be rainfall, irrigation used to water crops, or for supplying drinking water for animals, while the amount of water in the soil determines it capacity to support machinery and animals. We identify that UK agriculture is exposed to five main water-related risks: agricultural drought, scarcity of water resources, restrictions on the right to abstract water, excess soil water, and inundation. Projected milder, wetter winters and hotter, drier summers by the end of the century will change the frequency, persistence, or severity of each of these risks. This paper critically reviews and synthesizes the scientific literature on the impact of these risks on primary food production and the technological and managerial strategies employed to build resilience to these changing risks. At the farm scale, the emphasis has been on strategies to build robustness to reduce the impact of a water-related risk. However, collaborative partnerships allow for a more optimal allocation of water during times of scarcity. Enhancing cross-scale interactions, learning opportunities, and catchment-scale autonomy will be key to ensuring the agricultural system can build adaptive and transformational capacity
Keywords: water resources; irrigation; flooding; drought; drainage